2023
DOI: 10.1371/journal.pone.0280204
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding of dosing regimen instructions among patients with chronic diseases receiving polypharmacy at the University of Gondar comprehensive specialized hospital

Abstract: Background Misunderstanding dosage instructions in terms of dose, frequency, duration, or any other instruction with patients on polypharmacy is a common problem that leads to the irrational use of medications. This study aimed to assess the level of misunderstanding of dosing instructions among patients with chronic diseases receiving polypharmacy at the chronic outpatient pharmacy of the University of Gondar Compressive Specialized Hospital (UoGCSH). Methods An institutional-based cross-sectional survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This could be attributed to the increasing complexity of medication regimens, which in turn impacts patients’ medication adherence. The burden could be significant particularly in the Ethiopian population with most of the patients having a lower level of health literacy ( 40 , 41 ) and a higher level of misunderstanding of dosage regimen instructions ( 42 ). A part of this study also demonstrated that patients with higher regimen complexity scores had a lower quality of life ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the increasing complexity of medication regimens, which in turn impacts patients’ medication adherence. The burden could be significant particularly in the Ethiopian population with most of the patients having a lower level of health literacy ( 40 , 41 ) and a higher level of misunderstanding of dosage regimen instructions ( 42 ). A part of this study also demonstrated that patients with higher regimen complexity scores had a lower quality of life ( 43 ).…”
Section: Introductionmentioning
confidence: 99%